Potential Environmental Impact of Biodiesel Production from Palm Oil using LCA (Life Cycle Assessment) in Indonesia - Paminto, Ari; Karuniasa, Mahawan; Frimawaty, Evi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Primary energy production in Indonesia in 2018 consisting of petroleum, natural gas, coal and renewable energy reached 1,504 million BOE (Barrel of Oil Equivalent). Dependence on the use of fuel oil (BBM), especially in the transportation sector, is still high. The global commitment to reducing greenhouse gas emissions encourages the Indonesian government to support the role of new and renewable energy. Life cycle assessment (LCA) has become a popular technique applied to evaluate the environmental impact, energy consumption and GHG (Greenhouse Gas) emissions of biofuel production. To evaluate the life cycle impact of biodiesel, many steps have to be considered including land use change, plantation, milling, refining, fuel conversion. There have been several studies reporting the life cycle of palm oil production. However, most of them are still focused on GHG emissions and energy needs. Therefore, this paper will present LCA with broader impact categories of biodiesel production in Indonesia from the plantation phase to the production phase. Based on the analysis carried out, it can be concluded that the main contributor to the environmental impact of biodiesel production is the use of fertilizers at the plantation stage and the transesterification process at the biodiesel plant